Evaluation of Eimeria oocyst whole antigen vaccine and the enhancive effect of probiotic on broilers - ElBahy, Nasr; Khalafalla, Reda; ElKhatam, Ahmed; AbouLaila, Mahmoud (International Journal of Basic and Applied Sciences, 2014)
Chicken coccidiosis has great economic impacts on poultry industry. The present study was conducted to evaluate the effect of feeding probiotic (Biopellt-s) as well as Eimeria oocyst whole antigen vaccine by subcutaneous and intraperitoneal routes on body weight gain, lesion score, oocyst output, and phagocytic activity. One-day old broiler chicks were divided into seven equal groups (50 chicks each); control negative group (C-Ve), probiotic fed group (PRO), subcutaneous vaccinated group (S/C), intraperitoneal vaccinated group (I/P), S/C plus probiotic (S/C Pro), I/P plus probiotic (I/P Pro), and positive control group (C+Ve). At four weeks, chicks challenged with 12.000 sporulated oocysts. Vaccination decreases the lesion score and the oocyst output in S/C group (9000 oocyst/gram) and in I/P group (12500 oocyst/gram) compared with positive control (43500 oocyst/gram). S/C was more effective than I/P for controlling the infection. Probiotic supplementation resulted in significant increase in body weight gain (1323 gm) compared with positive control (1026.667 gm) and phagocytic activity (22.83 %) compared with positive control (16.08 %) while the vaccination was more effective than probiotic alone. S/C vaccination with probiotic was more effective than with I/P vaccination. Therefore, this study recommends the use of S/c or I/P vaccination regimens for coccidiosis. Keywords: Chicken Coccidiosis, Eimeria Oocyst Whole Antigen Vaccine, Probiotic.